Guided Reading Methods Assisted by Animation Videos to Improve Inferential and Textual Reading Comprehension - Tantowie, Tanto Aljauharie; Sunendar, Dadang; Hartati, Tatat; Nurmalihah, Laila (Jurnal Pendidikan Indonesia, 2024)
Reading comprehension ability is something that students need to master, but students' interest and ability in reading comprehension in Indonesia is still very low. This is partly caused by the less than optimal use of methods or media used by teachers. This research aims to determine the effect of video-assisted guided reading methods on elementary school students' reading comprehension abilities. The method used in this research is a Quasi Experimental method with a Non-Equivalent Control Group Design research design. The research sample consisted of 250 elementary school students who met the researchers' criteria. Data collection techniques in this research are tests, observation sheets and documentation studies. The instrument used is a text that has 2 topics, namely natural disasters and social inequality. Meanwhile, the data analysis used is the t test and regression test. The t-test was carried out to determine the effectiveness of the guided reading method. Apart from that, standard regression test data analysis was also carried out to see which type of understanding was superior, textual or inferential based on the type of text. The research results showed that the reading comprehension ability of students who received guided reading method intervention experienced a significant increase. Improved comprehension skills were seen in textual and inferential comprehension. Apart from that, readers with good inferential abilities also have a good level of comprehension. In contrast to readers whose understanding is textual, they have a good level of understanding only in the textual aspect.